Developing Materials of Thematic Quranic Interpretation based on Artificial Intelligence - Ardiansyah, Khaeruzzahir; Nurrohim, Ahmad (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
This study aims to develop and evaluate the Developing Materials Of Thematic Quranic Interpretation Based On Artificial Intelligence technology using the Perplexity platform. A descriptive approach is used to validate the learning media through evaluation by media experts and material experts. The validation results show that this media obtained an average feasibility score of 3.65 (feasible category). Media expert validation includes aspects of interface design, interactivity, and system stability, while material expert validation assesses the suitability of the content to the interpretation theme, accuracy of interpretation, and relevance to the curriculum. The results of the study revealed that AI technology in the Perplexity platform is able to increase learning efficiency through personalization of materials and access to relevant information in real time. This media also supports the development of students' critical thinking skills in assessing the accuracy of sources and understanding the themes of Al-Qur'an interpretation. The integration of this technology into learning results in a more interactive and effective learning experience. In conclusion, the AI-based "Thematic Interpretation" learning media is worthy of being used as a supporting tool for the religious education process. Further implementation is expected to include trials on a wider scale to measure its impact on student learning outcomes.